2009
DOI: 10.1016/j.ecolecon.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Fishery externalities and biodiversity: Trade-offs between the viability of shrimp trawling and the conservation of Frigatebirds in French Guiana

Abstract: Sustainable management of natural resources, and in particular fisheries, must take into account several conflicting objectives. This is the case in the French Guiana shrimp fishery for which profitability objectives imply a reduction in the fishing activity. On the one hand, this fishery has negative externalities on marine biodiversity due to discards. On the other hand, this fishery has positive externalities on the economy of the local community and interestingly enough on a protected seabird species in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…Conversely, this study found nestlings with a diet biased for lower trophic level prey to be in a better body condition than nestlings fed with higher trophic level prey (Morrison et al, 2014). In Frigatebirds, we would have expected depleted δ 13 C values in comparison to other species, given their attitude to feed far from the breeding colony and possibly in southern latitudes (Sebastiano et al, 2016), but they were not, possibly because Frigatebirds also feed on the shrimp fishery discards, a strategy commonly used in this colony (Martinet and Blanchard, 2009). …”
Section: Foraging Ecology and Trophic Nichementioning
confidence: 86%
“…Conversely, this study found nestlings with a diet biased for lower trophic level prey to be in a better body condition than nestlings fed with higher trophic level prey (Morrison et al, 2014). In Frigatebirds, we would have expected depleted δ 13 C values in comparison to other species, given their attitude to feed far from the breeding colony and possibly in southern latitudes (Sebastiano et al, 2016), but they were not, possibly because Frigatebirds also feed on the shrimp fishery discards, a strategy commonly used in this colony (Martinet and Blanchard, 2009). …”
Section: Foraging Ecology and Trophic Nichementioning
confidence: 86%
“…Taking all ecosystem and economic feedbacks into account might also reveal unforeseen trade-offs and externalities, like in the case of French Guiana, where the (economically sub-optimal) oversized trawl fishery for shrimps positively impacts endangered frigatebirds Fregata spp. (Martinet & Blanchard 2009). In the case of the Baltic Sea, we envisage a broadening of the scope of future work to an eco system level.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, there is a long history within decision theory, including multi-criteria and multi-objective analyses, of developing tools for decision-making where there are numerous and often competing objectives [33]. Multi-criteria analysis has been applied to numerous marine applications [34][35][36][37] and there has been recent progress applying these ideas to managing ecosystem services [20,[38][39][40][41]. However, there is not a synthesis of how tradeoff analysis can used in an EBM or MSP approach.…”
Section: Introductionmentioning
confidence: 99%